Correction: Rodrigues et al. Applying Remote Sensing, Sensors, and Computational Techniques to Sustainable Agriculture: From Grain Production to Post-Harvest. Agriculture 2024, 14, 161 - Dágila Melo Rodrigues; Paulo Carteri Coradi; Newiton da Silva Timm; Michele Fornari; Paulo Grellmann; Telmo Jorge Carneiro Amado; Paulo Eduardo Teodoro; Larissa Pereira Ribeiro Teodoro; Fábio Henrique Rojo Baio; José Luís Trevizan Chiomento (Agriculture)
The authors have recognized several errors in the original publication [...]